PERGESERAN KEKUASAAN NEGARA DAN RELASI ANTARSUBJEK DALAM CERPEN ORDE BARU DAN REFORMASI - Akhmad Rizqi Turama (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
The focus in this paper is how the state power’s perspective and inter subject relation in Danarto’s “Godlob” and Seno Gumira Ajidarma’s “Clara”. The first short story is the representation of Orde Baru while the second is the representation of reformation era. This paper uses two theories, Gramsci’s idea about Hegemony and the Foucault’s notion about power. The result of this research shows that there are changes in state hegemonic instrument, military discourse, state institute discourse, and inter subject relation from the Orde Baru to the reformation era.Keywords: short story, Orde Baru, Reformation, Gramsci, Foucault.